Zinc in Dermatology: Exploring Its Emerging Role in Enhancing Botulinum Toxin Formulations and Clinical Efficacy - Lacey Foster; Jose A. Foppiani; Helen Xun; Daniela Lee; Begum Utz; Angelica Hernandez Alvarez; Maria J. Domingo-Escobar; Iulianna C. Taritsa; Dominika Gavlasova; Theodore C. Lee; Gavin J. Lin; Umar Choudry; et al. (Current Issues in Molecular Biology)
This literature review provides a novel exploration of zinc’s multifaceted roles in dermatology, with a particular focus on its potential integration into botulinum toxin formulations—an area that remains relatively underexplored in clinical practice. Zinc is widely recognized for its critical functions in skin health, including morphogenesis, regeneration, and protection, and its use in aesthetic medicine offers a unique opportunity for innovation. Specifically, incorporating zinc into botulinum toxin formulations could enhance the efficacy and stability of these treatments. Although zinc has historically been used in topical dermatological products and systemic health interventions, its potential in cosmetic preparations, such as anti-aging therapies or non-invasive aesthetic treatments, remains under-researched. Emerging patents suggest promising formulations combining zinc with botulinum toxin that may improve product stability and extend therapeutic effects. While current studies on oral zinc supplementation present mixed results concerning its ability to prolong botulinum toxin effects, this underscores the need for more rigorous investigation in the realm of aesthetic medicine. Zinc’s well-established role in stabilizing dermatological products, such as sunscreens, and its applications in wound healing and skin regeneration, further highlights its potential for broader therapeutic uses beyond cosmetic applications. This review identifies a critical gap in the literature and calls for future research to optimize zinc concentrations and delivery methods specifically for aesthetic medical procedures, offering new insights into improving dermatological treatments beyond the scope of traditional cosmetic preparations.